2016
DOI: 10.1002/2016gl069261
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic observation of the onset of reactive‐infitration instability in an analog fracture

Abstract: Reactive‐infiltration instability plays an important role in many geophysical problems yet theoretical models have rarely been validated experimentally. We study the dissolution of an analog fracture in a simple microfluidic setup, with a gypsum block inserted in between two polycarbonate plates. By changing the flow rate and the distance between the plates, we are able to scan a relatively wide range of Péclet and Damkhöhler numbers, characterizing the relative magnitude of advection, diffusion, and reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 56 publications
(90 reference statements)
0
41
0
Order By: Relevance
“…In Garcia-Rios et al (2015) we observe all four phases: face dissolution (Figure 6a), compact wormholes (Figures 7a and 7b), a necked wormhole (Figure 7d, XCMT images), and uniform dissolution (Figure 6d). The microfluidic experiments reported by Osselin et al (2016) show an instability in the dissolution front (Figure 2a of their paper). Fingers are being formed, but the shapes of the fully developed wormholes were not reported.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In Garcia-Rios et al (2015) we observe all four phases: face dissolution (Figure 6a), compact wormholes (Figures 7a and 7b), a necked wormhole (Figure 7d, XCMT images), and uniform dissolution (Figure 6d). The microfluidic experiments reported by Osselin et al (2016) show an instability in the dissolution front (Figure 2a of their paper). Fingers are being formed, but the shapes of the fully developed wormholes were not reported.…”
Section: Discussionmentioning
confidence: 86%
“…accounts for experiments (Detwiler et al, 2003;Osselin et al, 2016) with only a single reactive surface (n = 1) as well as the remaining experiments (Elkhoury et al, 2013;Garcia-Rios et al, 2015) and simulations (n = 2). This definition of the Damköhler number accounts for varying length to aperture ratios (L∕h 0 ) and for the hindrance arising from reactant diffusion across the aperture (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reactive‐infiltration mechanism (see review in De Wit ()) was used to explain patterns observed in a variety of geological processes including oil recovery (Daccord et al, ), karst formation (Ortoleva et al, ; Szymczak, ), fluid ascent in the crust (Koulakov et al, ), melt migration (Jordan & Hesse, ; Hewitt, ; Hesse et al, ; Liang et al, ; Keller & Katz, ; Rudge et al, ; Schiemenz et al, ; Weatherley & Katz, ; Spiegelman et al, ), and inner core growth (Sumita et al, ). It also led to numerous studies aiming at reproducing instabilities in the laboratory (Osselin et al, ; Pec et al, ; Vardoulakis et al, ) and developing the theoretical framework to model this process (Szymczak & Ladd, , ; Wangen, ).…”
Section: Introductionmentioning
confidence: 99%